Clinical and microbiological characteristics of New Delhi MBL (NDM)-producing Klebsiella pneumoniae infections at the Hospital Geriátrico San Isidro Labrador EsSalud, 2018 - Buendia Sotelo, Victor Manuel (2020)
Objective: To determine the clinical and microbiological characteristics of seven (7) cases of New Delhi MBL (NDM)producing Klebsiella pneumoniae nosocomial infections at the Hospital Geriátrico San Isidro Labrador (HG SIL) from February to May 2018. Materials and methods: A descriptive and retrospective study conducted in elderly people with urinary infections, pneumonia, sacral ulcers and surgical wound infection who received multiple non-protocolized antibiotic therapy. The methods used to detect MBLs in the Klebsiella pneumoniae isolates that showed decreased sensitivity to carbapenems were the phenylboronic acid-based (PBA) and ethylenediaminetetraacetic acid-based (EDTA) double disk tests. The identification of the NDM gene was performed by polymerase chain reaction at the Instituto Nacional de Salud. Results: In total, the seven cases were positive for the NDM gene and resistant to meropenem, which confirmed the epidemic outbreak. Mortality accounted for 28.6 % (2 of 7 patients) of the cases. However, due to the presence of comorbidities in all cases, the attributable mortality could not be determined. Conclusions: Labs have a key initial role for detecting and classifying the carbapenemases and the measures of comprehensive control of infections. The aforementioned cases are the first ones reported in our healthcare network.